2021
DOI: 10.1038/s41393-021-00689-3
|View full text |Cite
|
Sign up to set email alerts
|

Community-based wheelchair caster failures call for improvements in quality and increased frequency of preventative maintenance

Abstract: Study design Secondary data analysis of wheelchair failures and service repair logs from a network of wheelchair suppliers. Objective To determine the frequency of wheelchair caster failures and service repairs across wheelchair manufacturers and models and investigate the relationships between them. Setting Wheelchair caster failures and service repairs occurred in the community. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Preventative maintenance reduces the frequency of wheelchair failures and breakdowns, thus preventing adverse health consequences to older users [ 7 , 16 , 17 ]. To encourage maintenance practices and compliance, we are leveraging the existing capabilities of smartphones and sensors and developing an mHealth app called WheelTrak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preventative maintenance reduces the frequency of wheelchair failures and breakdowns, thus preventing adverse health consequences to older users [ 7 , 16 , 17 ]. To encourage maintenance practices and compliance, we are leveraging the existing capabilities of smartphones and sensors and developing an mHealth app called WheelTrak.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, although wheelchairs play a significant role in the lives of older adults and people with locomotor disabilities, they are known to break down frequently. Cross-sectional study findings over the past 2 decades show that approximately 45% to 88% of wheelchair users experience wheelchair part failures every 6 months owing to failures of wheelchair casters, rear wheels, brakes, frames, and seating systems [2][3][4][5][6][7]. Comparatively, in low-and middle-income countries, where rehabilitation services are scarce and outdoor environments are adverse, part failures occur every 2 to 3 months [8][9][10][11][12][13].…”
Section: The Calamity Of Wheelchair Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…7 , 9 , 10 Recent wheelchair failure data collection studies have found that caster stem bearings fracture within 2 years of use in adverse environments as well as in resourced settings. 11 , 12 Models like Matching Person and Technology highlights that a lack of consideration for an individual’s needs can lead to improper use, total abandonment, or injury. 13 These premature and frequent failures of wheelchair caster bearings can be attributed to a lack of consideration of individuals’ specific environments during product design, testing, and assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-reduction engineering practices in the wheelchair industry may have led to design and selection of low-cost, substandard caster parts that experience different failure modes including seized bearings, damaged bolts, fractured wheels and forks and worn-out tires and fasteners. 10 , 11 Stem and axle bearings are subjected to rapid fatigue and stress as wheelchairs are exposed to corrosion, shocks, high temperatures, and dirt especially during use in adverse environments. 14 , 15 Bearing fractures can lead to a cascade of high-risk failures with caster stems, bolts, and forks as they experience stresses higher than the ultimate tensile strength of their materials.…”
Section: Introductionmentioning
confidence: 99%